Tuberculosis and COVID-19 Dually Affect Human Th17 Cell Immune Response - Anna Starshinova; Igor Kudryavtsev; Artem Rubinstein; Anna Malkova; Irina Dovgaluk; Dmitry Kudlay (Biomedicines, 2023)
COVID-19 infection not only profoundly impacts the detection of tuberculosis infection (Tbc) but also affects modality in tuberculosis patient immune response. It is important to determine immune response alterations in latent tuberculosis infection as well as in SARS-CoV-2-infected tuberculosis patients. Such changes may have underlying effects on the development and course of further tuberculosis. Here, we aimed to review the characteristics of immune response in TB patients or convalescent COVID-19 patients with latent TB infection (LTBI). Materials and Methods. We analyzed the features of immune response in tuberculosis and COVID-19 patients. For this, we analyzed publications released from December 2019 to March 2023; those which were published in accessible international databases (“Medline”, “PubMed”, “Scopus”) and with keywords such as “COVID-19”, “SARS-CoV-2”, “tuberculosis”, “pulmonary tuberculosis”, “latent tuberculosis infection”, “Treg”, “follicular Treg”, and “Treg subsets”, we considered. Results. Through our analysis, we found that tuberculosis patients who had been infected with COVID-19 previously and elevated Th1 and Th2 cell levels. High levels of Th1 and Th2 cells may serve as a positive marker, characterizing activated immune response during TB infection. COVID-19 or post-COVID-19 subjects showed decreased Th17 levels, indicating a lack of tuberculosis development. Moreover, the typical course of tuberculosis is associated with an increase in Treg level, but COVID-19 contributes to a hyperinflammatory response. Conclusion. According to the data obtained, the course of tuberculosis proceeds in a dissimilar way due to the distinct immune response, elicited by SARS-CoV-2. Importantly, the development of active tuberculosis with a severe course is associated with a decline in Treg levels. Both pathogens lead to disturbed immune responses, increasing the risk of developing severe TB. The insights and findings of this paper may be used to improve the future management of individuals with latent and active tuberculosis.